Holding member and method for manufacturing the same

By forming a low-density alumina and silicate base layer on the side of the AlN ceramic substrate and forming a ceramic insulating layer on it, the problem of difficulty in forming a high-reliability insulating layer in semiconductor chip manufacturing is solved, and the high adhesion and shear strength of the ceramic insulating layer are achieved, and the insulation performance of the chip is improved.

JP2025039363APending Publication Date: 2025-03-21NITERRA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023146425
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

When manufacturing a semiconductor chip, it is difficult to form a high-reliability insulating layer on the side surface of the AlN ceramic substrate by thermal spraying.

Method used

A low-density alumina and silicate base layer is formed on the sides of the AlN ceramic substrate, and a ceramic insulating layer is formed thereon by thermal spraying. This base layer forms a strong adhesion layer by absorbing silica in the air, which improves the adhesion and shear strength of the ceramic insulating layer.

Benefits of technology

The adhesion and shear strength of the ceramic insulating layer on the AlN ceramic substrate are improved, the peel resistance and reliability of the insulating layer are enhanced, and the insulation performance of the semiconductor chip is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039363000001_ABST
    Figure 2025039363000001_ABST
Patent Text Reader

Abstract

To provide a technique for forming an insulating layer by thermal spraying on the side surface of a joint between an AlN ceramic base material and a substrate.SOLUTION: An electrostatic chuck module 100 includes a ceramic base material 110 primarily composed of AlN, an electrostatic adsorption electrode 124 embedded in the ceramic base material 110, a substrate 150 joined to a main surface (upper surface 111 or lower surface 113) of the ceramic base material 110, a base film 160 primarily composed of alumina and silica and covering a side surface 114 of the ceramic base material 110, and a ceramic sprayed film 180 primarily composed of insulating ceramics formed on the base film 160.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a retaining member and a method for manufacturing the retaining member. [Background technology]

[0002] Conventionally, as an example of a holding member, there has been known an electrostatic chuck that includes a metal base material, an insulating layer disposed on the upper surface of the metal base material, and a chuck electrode (electrode for electrostatic attraction) disposed on the insulating layer (see, for example, Patent Document 1).

[0003] In the electrostatic chuck described in Patent Document 1, the metal base material is made of, for example, titanium, aluminum, molybdenum, etc. The insulating layer is made of aluminum oxide (Al 2 O 3 The electrostatic chuck described in Patent Document 1 further includes a dielectric layer that covers the upper and side surfaces of the assembly of the chuck electrode, the insulating layer, and the metal base material. The dielectric layer is a sprayed film and functions as a protective layer for the electrostatic chuck. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 7234459 Summary of the Invention [Problem to be solved by the invention]

[0005] In a so-called sprayed electrostatic chuck in which an insulating layer formed on a metal base is formed by thermal spraying, such as the electrostatic chuck described in Patent Document 1, it is known that a dielectric film covering the insulating layer and the side surface of the metal base can be formed relatively easily by thermal spraying. In recent years, in a manufacturing process of semiconductor wafers, a wafer holding member is sometimes used, which includes a ceramic mounting member having an AlN ceramic base material in which an electrostatic attraction electrode (or a high-frequency electrode) is embedded, and a base body bonded to the lower surface of the mounting member. In such a holding member, it is desired to improve insulation by forming an insulating layer on the side surface of the bonded body of the AlN ceramic base material and the base body. In order to form a highly reliable insulating layer, it is preferable to form the insulating layer by thermal spraying, but it has been difficult to form an insulating layer on an AlN ceramic base material by thermal spraying.

[0006] The present invention has been made in view of the above circumstances, and has an object to provide a technique for forming an insulating layer by thermal spraying on the side surface of a bonded body of an AlN ceramic base and a substrate. [Means for solving the problem]

[0007] According to an aspect of the present invention, a plate-shaped mounting member having an upper surface, a lower surface facing the upper surface in a vertical direction, and a side surface connecting the upper surface and the lower surface in the vertical direction, the plate-shaped mounting member having an AlN ceramic containing AlN as a main component and an electrode to be disposed on the AlN ceramic; a plate-shaped base having a main surface joined to the upper surface or the lower surface of the mounting member; a base film containing alumina and silica as main components and covering the side surface of the mounting member; A holding member is provided, which includes a thermal sprayed film mainly composed of insulating ceramics formed on the base film. Effect of the Invention

[0008] Generally, it is very difficult to form a thermal spray coating mainly composed of insulating ceramics directly on the side surface of an AlN ceramic. In contrast, in this embodiment, a base film mainly composed of alumina and silica is formed on the side surface of the AlN ceramic. When the base film mainly composed of alumina and silica solidifies, CO 2 It absorbs water and precipitates gel-like silicic acid (releasing water and solidifying), which shows strong adhesive strength. Therefore, the undercoat film can be formed on the side of the AlN ceramics. Furthermore, the density of the undercoat film is 2.15 to 2.30 g / cm 3 Since the density is relatively low, the sprayed insulating ceramic particles in a molten state bite into the pores of the base film, creating an anchor effect that increases the peel strength and shear strength of the sprayed film. This improves the peel resistance of the sprayed film that covers the side surface of the AlN ceramic, and improves the insulation reliability and durability of the holding member. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a perspective view of an electrostatic chuck module 100. [Diagram 2] FIG. 2 is a schematic diagram of the electrostatic chuck module 100. As shown in FIG. [Diagram 3] FIG. 3 is a schematic explanatory diagram showing the shape of the electrostatic attraction electrode 124. As shown in FIG. [Figure 4] 1(a) to 1(e) are diagrams showing a flow of a method for producing the ceramic base 110. FIG. [Diagram 5] 1(a) to 1(d) are diagrams showing the flow of another method for producing the ceramic base 110. FIG. [Figure 6] FIG. 6 is a flowchart for explaining a manufacturing method of the electrostatic chuck module 100. [Figure 7] FIG. 7 is a schematic explanatory diagram showing the shape of the high-frequency electrode 126. As shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] <Electrostatic chuck module 100> An electrostatic chuck module 100 according to this embodiment will be described with reference to FIGS. 1 and 2. The electrostatic chuck module 100 according to this embodiment is an example of a holding member for adsorbing and holding a semiconductor wafer such as a silicon wafer (hereinafter, simply referred to as a wafer 10). In the following description, a top-bottom direction 5 is defined based on a state in which the electrostatic chuck module 100 is installed so as to be usable (the state in FIG. 1). As shown in FIG. 1, the electrostatic chuck module 100 according to this embodiment mainly includes a ceramic base material 110, an electrostatic adsorption electrode 124 (see FIGS. 2 and 3), a base body 150, a base film 160 (see FIG. 2), and a ceramic sprayed film 180 (see FIG. 2).

[0011] The ceramic base 110 is a member having a circular plate shape with a diameter of 12 inches (approximately 300 mm), and the wafer 10 to be held is placed on its upper surface 111. In FIG. 1, the wafer 10 and the ceramic base 110 are shown separated from each other to make the drawing easier to see. In this embodiment, the ceramic base 110 is formed of a sintered body of AlN ceramics containing aluminum nitride (AlN) as the main component. Here, containing AlN as the main component means that the AlN content is 50% or more. The center line average roughness (Ra) of the upper surface 111 and the side surface 114 of the ceramic base 110 is less than 1.0 μm.

[0012] Although not shown in the figure, the upper surface 111 of the ceramic substrate 110 can be arranged with a circular ring-shaped protrusion arranged on the outer periphery (outer edge) and a plurality of cylindrical protrusions arranged inside the circular ring-shaped protrusion.

[0013] A gas flow path (not shown) can be formed inside the ceramic base 110. The gas flow path can be used as a flow path for supplying gas to a space (gap) defined by the upper surface 111 of the ceramic base 110 and the lower surface of the wafer 10. Conversely, gas can be exhausted from the space (gap) defined by the upper surface 111 of the ceramic base 110 and the lower surface of the wafer 10 through the gas flow path. At this time, the pressure difference between the pressure outside the gap and the pressure inside the gap can be adjusted by adjusting the exhaust pressure. This allows the wafer 10 to be adsorbed toward the upper surface of the ceramic base 110.

[0014] 2, an electrostatic attraction electrode 124 is embedded inside the ceramic base 110. The electrostatic attraction electrode 124 can be embedded at a position 0.1 mm to 2.0 mm downward from the upper surface 111 of the ceramic base 110. In other words, the thickness of the ceramic insulating layer from the upper surface 111 of the ceramic base 110 to the electrostatic attraction electrode 124 can be 0.1 mm or more and 2.0 mm or less.

[0015] 3, the electrostatic attraction electrode 124 has two semicircular electrodes 124a and 124b arranged to face each other with a predetermined distance between them, and has a generally circular shape as a whole. In this embodiment, the outer diameter of the electrostatic attraction electrode 124 is 292 mm. The wafer 10 can be electrostatically attracted by applying a predetermined voltage (e.g., ±500 V) to each of the electrodes 124a and 124b. In this embodiment, the ceramic base 110 and the electrostatic attraction electrode 124 form an electrostatic chuck (an example of a mounting member of the present invention).

[0016] 2, a base 150 is bonded to the lower surface 113 of the ceramic base 110. The base 150 has a circular plate shape with the same diameter as the ceramic base 110. In this embodiment, the base 150 is made of molybdenum (Mo). The base 150 is made of a metal material having a relatively small coefficient of linear expansion (CTE) (CTE<1.2×10), such as molybdenum, tungsten (W), tantalum (Ta), or SUS. -5 / °C). In this case, since the difference in thermal expansion coefficient with AlN ceramics is not large, it is possible to directly bond the upper surface 151 of the base 150 and the lower surface 113 of the ceramic base material 110 under high temperature and pressure without using a bonding agent. Alternatively, they can be bonded using an adhesive, solder, brazing material, or the like. In contrast, when the base 150 is made of a metal material with a relatively large coefficient of linear expansion (CTE) such as an Al alloy (CTE≧1.2×10 -5 / °C). In this case, since the difference in thermal expansion coefficient with AlN ceramics becomes large, it is difficult to directly bond the upper surface 151 of the base 150 and the lower surface 113 of the ceramic base material 110, but they can be bonded by adhesive, solder, brazing material, etc.

[0017] 2, an undercoat film 160 is formed on the side surface 114 of the ceramic substrate 110 and the side surface 154 of the base body 150. In this embodiment, the undercoat film 160 is formed so as to cover the entire side surface 114 of the ceramic substrate 110 and the entire side surface 154 of the base body 150. The undercoat film 160 is made of alumina (Al 2 O 3 ) and silica (silicon dioxide, SiO 2 A ceramic adhesive based on alumina and water glass (silicic anhydride (SiO 2 ) and sodium oxide (Na 2 Ceramic adhesives made from alumina and silica (a mixture of CO2 and water) can be used. 2It exhibits strong adhesive strength because it absorbs water and precipitates gel-like silicic acid (releases water and solidifies). Therefore, the undercoat film 160 can also be formed on the side surface 114 of the ceramic base material 110, which is the surface of the AlN ceramic. In this embodiment, the undercoat film 160 has a thickness of 100 μm.

[0018] A ceramic sprayed film 180 is formed on the upper surface of the base film 160. The ceramic sprayed film 180 is made of alumina (Al 2 O 3 ), Y 2 O 3 In this embodiment, the ceramic sprayed film 180 is an alumina sprayed film, and has a thickness of 400 μm. The density of the base film 160 is 2.15 to 2.30 g / cm3 due to the pores formed in the base film 160. 3 Since the base film 160 contains pores and has a low density, the molten spray particles made of insulating ceramics bite into the pores of the base film 160, creating an anchor effect, which can increase the peel strength and shear strength of the ceramic sprayed film 180.

[0019] Next, a method for manufacturing the electrostatic chuck module 100 will be described. In the following, a case where the ceramic base 110 is made of aluminum nitride will be described as an example. For the sake of simplicity, it is assumed that only the electrostatic attraction electrode 124 is embedded in the ceramic base 110.

[0020] First, a method for manufacturing the ceramic base material 110 will be described. As shown in FIG. 4(a), granulated powder Q mainly composed of aluminum nitride (AlN) powder is placed in a bed-equipped carbon mold 601 and pre-pressed with a punch 602. The granulated powder Q contains 5 wt % or less of a sintering aid (for example, Y 2 O 3) is preferably included. As the electrostatic adsorption electrode 124, a Mo foil or plate having a thickness of 0.05 mm or more is prepared. At this time, a plurality of through holes can be formed in the electrostatic adsorption electrode 124 by etching or the like. Alternatively, the electrostatic adsorption electrode 124 can be formed by a mesh woven with Mo wires. Next, as shown in FIG. 4(b), the electrostatic adsorption electrode 124 cut into a predetermined shape is placed on the pre-pressed granulated powder Q. The electrostatic adsorption electrode 124 is placed so as to be parallel to a surface perpendicular to the pressure direction (the bottom surface of the bed-equipped mold 601). At this time, W pellets or Mo pellets may be embedded at the position of the terminal 124T (see FIG. 3) of the electrostatic adsorption electrode 124.

[0021] As shown in FIG. 4(c), granulated powder Q is further poured into the bed-type mold 601 so as to cover the electrostatic adsorption electrode 124, and pressed and molded with a punch 602. At this time, the amount of granulated powder Q covering the electrostatic adsorption electrode 124 can be adjusted so that the electrostatic adsorption electrode 124 is embedded at a depth of 0.3 mm or more. Next, as shown in FIG. 4(d), the granulated powder Q in which the electrostatic adsorption electrode 124 is embedded is fired in a pressed state. The pressure applied during firing is preferably 1 MPa or more. In addition, firing is preferably performed at a temperature of 1800° C. or more. Note that firing can also be performed multiple times. Next, as shown in FIG. 4(e), blind holes are drilled up to the electrostatic adsorption electrode 124 in order to form the terminal 124T. Note that, if a pellet is buried, blind holes are drilled up to the pellet. Furthermore, a through hole for forming a gas flow path may be formed as necessary. In this case, a ceramic base material 110 having a gas flow path formed therein can be produced.

[0022] The ceramic substrate 110 can also be manufactured by the following method. As shown in Fig. 5(a), a binder is added to aluminum nitride granulated powder Q, which is then CIP molded and processed into a disk shape to produce an aluminum nitride compact 610. Next, as shown in Fig. 5(b), the compact 610 is degreased to remove the binder.

[0023] As shown in FIG. 5(c), a recess 611 for embedding the electrostatic adsorption electrode 124 is formed in the degreased molded body 610. The recess 611 may be formed in advance in the molded body 610. As described above, a Mo foil or plate having a thickness of 0.05 mm or more is prepared as the electrostatic adsorption electrode 124, and a plurality of through holes 128 are formed in the electrostatic adsorption electrode 124 by etching or punching. Alternatively, the electrostatic adsorption electrode 124 is formed by a mesh woven with Mo wires. The electrostatic adsorption electrode 124 is disposed in the recess 611 of the molded body 610, and another molded body 610 is laminated thereon. At this time, the thickness of the other molded body 610 can be adjusted so that the electrostatic adsorption electrode 124 is embedded at a depth of 0.3 mm or more. Next, as shown in FIG. 5(d), the laminated molded bodies 610 sandwiching the electrostatic adsorption electrode 124 are fired in a pressed state to produce a fired body. The pressure applied during firing is preferably 1 MPa or more. Also, firing is preferably performed at a temperature of 1800°C or more. Note that firing can be performed multiple times. The steps after producing the fired body are the same as those described above, so the explanation will be omitted.

[0024] The upper surface 111, the lower surface 113, and the side surface 114 of the ceramic base material 110 thus formed are ground and polished. At this time, the distance in the vertical direction 5 from the upper surface 111 of the ceramic base material 110 to the electrostatic attraction electrode 124 can be adjusted. Furthermore, by performing a sandblasting process on the upper surface 111, it is possible to form a plurality of convex portions and an annular convex portion on the upper surface 111. Note that, although sandblasting is a suitable processing method for forming the plurality of convex portions and the annular convex portion, other processing methods can also be used.

[0025] 6, an upper surface 151 of a base 150 is bonded to a lower surface 113 of a ceramic base 110 formed by the above-mentioned procedure (S1). As described above, the base 150 is made of a metal material having a relatively small coefficient of linear expansion (CTE) (CTE<1.2×10), such as molybdenum, tungsten (W), tantalum (Ta), or SUS. -5 / °C), the upper surface 151 of the base 150 and the lower surface 113 of the ceramic base 110 can be directly bonded to each other. Alternatively, they can be bonded to each other by adhesive, solder, brazing material, or the like. When the base 150 is made of a metal material having a relatively large coefficient of linear expansion (CTE) such as an Al alloy (CTE≧1.2×10 -5 / °C), they can be joined by adhesive, solder, brazing material, etc.

[0026] Next, a ceramic adhesive containing alumina and silica as main components is applied to the side surface 114 of the ceramic substrate 110 and the side surface 154 of the base body 150 to form the undercoat film 160 (S2). The undercoat film 160 may have a thickness of, for example, 20 μm to 200 μm. The undercoat film 160 preferably has a thickness of about 100 μm. The undercoat film 160 can be cured at room temperature, but can also be cured by subjecting it to a heat treatment (for example, a heat treatment at 93° C. for 2 hours or more).

[0027] When forming the undercoat film 160 on the side surface 114 of the ceramic substrate 110 and the side surface 154 of the base 150, the undercoat film 160 can be formed over the entire side surface 114 of the ceramic substrate 110 and the entire side surface 154 of the base 150. Alternatively, the undercoat film 160 can be formed so as to cover the boundary portion between the side surface 114 of the ceramic substrate 110 and the side surface 154 of the base 150.

[0028] Next, a ceramic sprayed film 180 mainly composed of insulating ceramics is formed on the upper surface of the base film 160 (S3). In this embodiment, a ceramic sprayed film of alumina is formed as the ceramic sprayed film 180 by spraying alumina spray particles onto the base film 160. Normally, it is difficult to form the ceramic sprayed film 180 directly on the side surface 114 of the ceramic base material 110 mainly composed of AlN ceramics. In this embodiment, the base film 160 is formed on the side surface 114 of the ceramic base material 110, and the ceramic sprayed film 180 is further formed thereon. As described above, since the base film 160 has a low density, the sprayed particles in a molten state made of insulating ceramics (alumina in this embodiment) bite into the pores of the base film 160, creating an anchor effect, and the peel strength and shear strength of the ceramic sprayed film 180 can be increased.

[0029] <Effects of the embodiment> In the above embodiment, the electrostatic chuck module 100 includes a ceramic base 110 mainly composed of AlN, an electrostatic attraction electrode 124 embedded in the ceramic base 110, a base 150 joined to a main surface (upper surface 111 or lower surface 113) of the ceramic base 110, a base film 160 mainly composed of alumina and silica covering a side surface 114 of the ceramic base 110, and a ceramic sprayed film 180 mainly composed of insulating ceramics formed on the base film 160.

[0030] It is very difficult to form the ceramic sprayed film 180 directly on the side surface 114 of the ceramic substrate 110. In contrast, in this embodiment, the base film 160 mainly composed of alumina and silica is formed on the side surface 114 of the ceramic substrate 110. When the base film 160 mainly composed of alumina and silica solidifies, CO 2 It absorbs water and precipitates gel-like silicic acid (releases water and solidifies), and therefore exhibits strong adhesive strength. Therefore, the undercoat film 160 can be formed on the side surface 114 of the ceramic substrate 110, which is the surface of the AlN ceramic. Furthermore, the density of the undercoat film 160 is 2.15 to 2.30 g / cm3 Since the density is relatively low, the molten sprayed particles of the insulating ceramic bite into the pores of the base film 160 to create an anchor effect, thereby increasing the peel strength and shear strength of the ceramic sprayed film 180. This improves the peel resistance of the ceramic sprayed film 180 covering the side surface 114 of the ceramic substrate 110, and improves the insulation reliability and durability of the electrostatic chuck module 100.

[0031] In the above embodiment, an alumina sprayed film can be formed as the insulating ceramic sprayed film 180. The base film 160 contains alumina and silica as main components. When the ceramic sprayed film 180 is a sprayed film of alumina, which is a component contained in the base film 160, the adhesion between the base film 160 and the ceramic sprayed film 180 can be improved.

[0032] In the above embodiment, the undercoat film 160 covers the boundary between the side surface 114 of the ceramic substrate 110 and the side surface 154 of the base 150. This makes it possible to improve the reliability and durability of insulation, particularly in the boundary portion between the side surface 114 of the ceramic substrate 110 and the side surface 154 of the base 150.

[0033] In the above embodiment, the base 150 contains Mo as a main component. In this case, since the base 150 contains Mo, which is a high melting point metal, as a main component, it is possible to improve the high temperature resistance of the electrostatic chuck module 100. In addition, since the base 150 contains Mo as a main component, it is possible to reduce the difference in thermal expansion coefficient with AlN ceramics, and it is possible to directly bond the upper surface 151 of the base 150 and the lower surface 113 of the ceramic base 110.

[0034] In the above embodiment, the manufacturing method of the electrostatic chuck module 100 includes joining the upper surface 151 of the base body 150 to the lower surface 113 of the ceramic substrate 110 (FIG. 6: S1), applying a ceramic adhesive mainly composed of alumina and silica to the side surface 114 of the ceramic substrate 110 and the side surface 154 of the base body 150 to form a base film 160 (FIG. 6: S2), and forming a ceramic sprayed film 180 mainly composed of insulating ceramics on the upper surface of the base film 160 (S3).

[0035] Normally, it is difficult to form the ceramic sprayed film 180 directly on the side surface 114 of the ceramic base 110 mainly composed of AlN ceramics. In this embodiment, the base film 160 is formed on the side surface 114 of the ceramic base 110, and the ceramic sprayed film 180 is further formed thereon. In this case, the peel strength and shear strength of the ceramic sprayed film 180 can be increased due to an anchor effect in which the sprayed particles in a molten state made of insulating ceramic bite into the pores of the base film 160. This can improve the peel resistance of the ceramic sprayed film 180 covering the side surface 114 of the ceramic base 110, and can improve the reliability and durability of the insulation of the electrostatic chuck module 100.

[0036] <Modification form> The above-described embodiment is merely an example and may be modified as appropriate. For example, the shape, size, and thickness of the electrostatic adsorption electrode 124 are not limited to those in the above-described embodiment and may be modified as appropriate. Also, instead of the electrostatic adsorption electrode 124 or in addition to the electrostatic adsorption electrode 124, a high-frequency electrode 126 may be embedded in the ceramic base material 110. As shown in FIG. 7, the high-frequency electrode 126 has a circular shape. The outer diameter of the high-frequency electrode 126 may be, for example, 298 mm. By applying a predetermined high-frequency voltage to the high-frequency electrode 126, plasma can be generated above the ceramic base material 110.

[0037] The shape, thickness, etc. of the ceramic base 110 may be changed as appropriate. The position and / or number of the annular convex portion and the multiple convex portions provided on the upper surface 111 of the ceramic base 110 may be changed as appropriate depending on the application, action, and function. The annular convex portion does not necessarily have to be provided, and the multiple convex portions may be distributed over the entire surface of the upper surface 111 of the ceramic base 110.

[0038] In the above embodiment, the electrostatic attraction electrode 124 is formed of a molybdenum (Mo) foil, plate, or mesh woven with Mo wires. However, the present invention is not limited to such an embodiment. The electrostatic attraction electrode 124 can be formed of a heat-resistant metal (high melting point metal) such as a mesh or foil woven with wires of tungsten (W), molybdenum, and / or an alloy containing tungsten.

[0039] In the above embodiment, the base 150 is made of a metal material having a relatively small coefficient of linear expansion (CTE) (CTE<1.2×10), such as molybdenum, tungsten (W), tantalum (Ta), or SUS. -5 / ℃), or metal materials with a relatively large coefficient of linear expansion (CTE) such as Al alloys (CTE ≥ 1.2 × 10 -5 / ° C. However, the base 150 is not limited to being made of such a metal material. For example, the base 150 can also be made of a ceramic material such as SiC.

[0040] Although the present invention has been described above using the embodiment and its modified form, the technical scope of the present invention is not limited to the above description. It is obvious to those skilled in the art that various modifications or improvements can be made to the above embodiment. It is also clear from the claims that such modifications or improvements can be included in the technical scope of the present invention.

[0041] The order of execution of each process in the manufacturing method shown in the specification and drawings is not particularly specified, and may be any order unless the output of a previous process is used in a subsequent process. For convenience, even if the description uses "first," "next," etc., it does not mean that the process must be performed in that order. [Explanation of symbols]

[0042] 100 Electrostatic Chuck Module 110 Ceramic substrate 124 Electrostatic Adsorption Electrode 126 High Frequency Electrodes

Claims

1. a plate-shaped mounting member having an upper surface, a lower surface facing the upper surface in a vertical direction, and a side surface connecting the upper surface and the lower surface in the vertical direction, the plate-shaped mounting member having an AlN ceramic mainly composed of AlN and an electrode disposed on the AlN ceramic; a plate-shaped base having a main surface joined to the upper surface or the lower surface of the mounting member; a base film containing alumina and silica as main components and covering the side surface of the mounting member; a thermal spray coating formed on the base coating and containing insulating ceramics as a main component, said retaining member comprising:

2. 2. The holding member according to claim 1, wherein the insulating ceramic is alumina.

3. The holding member according to claim 1 , wherein the base film is disposed so as to cover a boundary between the side surface of the mounting member and the side surface of the base body.

4. The retaining member according to any one of claims 1 to 3, wherein the base contains Mo as a main component.

5. laminating and bonding a plate-shaped substrate and a mounting member having a plate-shaped AlN ceramic mainly composed of AlN and an electrode to be placed on the AlN ceramic; forming a base film mainly composed of alumina and silica on a side surface of the plate-shaped mounting member; forming a thermal sprayed film containing insulating ceramics as a main component on the base film.

Citation Information

Patent Citations

  • Electrostatic chuck and processing device

    JP7234459B2